Determining Effects of Superfine Sheep wool in INfantile Eczema (DESSINE): a randomized paediatric crossover study. (12th June 2017) - Su, J.C.; Dailey, R.; Zallmann, M.; Leins, E.; Taresch, L.; Donath, S.; Heah, S.S.; Lowe, A.J.
Summary: Background: Despite limited evidence, woollen clothing has traditionally been considered to be an irritant that should be avoided by individuals with atopic dermatitis (AD). Wool fibres come in a range of diameters, and have beneficial thermodynamic and moisture transport properties. Objectives: This study examines the effects of superfine merino wool on symptoms in participants with mild‐to‐moderate AD. Methods: The trial was a 12‐week, randomized, assessor‐blinded, crossover, prospective, cohort study of 39 patients with mild‐to‐moderate AD, aged between 4 weeks and 3 years, comparing superfine merino wool ensembles with standard cotton clothing chosen by parents. Participants were assigned to wool or cotton clothing and assessed every 3 weeks for 6 weeks, before crossing over to wear the other clothing material for a further 6‐week period, with similar 3‐weekly reviews. The primary end point was the SCORing Atopic Dermatitis (SCORAD) index after each 6‐week period, with Atopic Dermatitis Severity Index (ADSI), Infants' Dermatitis Quality Of Life Index (IDQOL) and topical steroid use as secondary end points to measure AD severity and quality of life. Results: Overall, compared with baseline, superfine wool ensembles were associated with a reduction in mean SCORAD of 2·5 [95% confidence interval (CI) −4·7 to −0·4] at 3 weeks and 7·6 (95% CI −10·4 to −4·8) at 6 weeks when compared with the cotton ensembles. A similar change was observed in ADSI and IDQOL scores for the same period. Body steroid use was also reduced. Conversely, changing ensembles from wool to cotton resulted in an increase in scores. Conclusions: Superfine merino wool may assist in the management of childhood AD. Abstract : What's already known about this topic? There are few published reports of the effects of wool on atopic dermatitis, and these papers date back to the 1950s when reporting did not meet current standards. Since then, improvements in specification of wool‐fibre diameter and in wool processing have enabled the production of less irritant clothing, which is also less contaminated by allergens. There is little available clinical evidence for adverse or beneficial effects of superfine wool. What does this study add? This study challenges generalizations that wool is to be avoided by children with eczema. This is the first original clinical study to examine the clinical effects of superfine merino wool on (childhood) atopic dermatitis. This clinical study highlights the need for further studies on the effects of clothing, and of the microenvironment between clothing and the skin, on atopic dermatitis. Respond to this article Plain language summary available online